Public Attention Index of Air Pollution Exposure from PM2.5 in Thailand - Pailin Suntigul; Sittidaj Pongkijvorasin (Applied Environmental Research, 2025)
Thailand faces a persistent PM2.5 challenge, with pollution levels consistently exceeding the World Health Organization’s guidelines. In response, the Thai government has made air pollution a national priority, implementing various policies and city-level plans to reduce exposure. These policies are often temporary and do not fully address root causes, whereas the limited monitoring coverage across Thailand restricts a comprehensive assessment of PM2.5 exposure severity. This study addresses the data gap by constructing a public attention index for PM2.5, using internet search data from Google Trends, to quantify public awareness and concern regarding PM2.5 exposure. This index aims to improve the understanding of PM2.5 exposure across Thailand and support more effective air quality management strategies. The findings indicate a statistically significant positive relationship between public attention, PM2.5 pollution levels, willingness to pay for PM2.5 reduction, and economic and social costs associated with PM2.5. The PAI_PM2.5 index serves as a valuable tool for policymakers, offering a data-driven method to align public perceptions with the true severity of pollution issues. The results further indicate that public attention is notably high in severely impacted areas, particularly Bangkok and the northern provinces, yet reveal an awareness gap in regions with significant pollution but low public concern. These findings have important policy implications, highlighting the need for targeted public awareness campaigns and specialized initiatives to improve air quality.